FRI0345 Tapering MTX in Patients with RA Using TNFI Treatment is Possible. (9th June 2015) - Manders, S.; van de Laar, M.; Rongen-van Dartel, S.; Bos, R.; Visser, H.; Brus, H.; Jansen, T.; Vonkeman, H.; van Riel, P.; Kievit, W.
Abstract : Background: Nowadays the focus is on tapering or stopping biological treatment in patients with rheumatoid arthritis (RA) because of the cost reduction. However, the use of methotrexate (MTX) can cause considerable burden for patients, therefore the quality of life of patients would increase if the MTX could be tapered or stopped. Objectives: The objective of this study was: 1. to analyse if patients taper or stop MTX in daily practice while they are using Tumor Necrosis Factor inhibitor (TNFi) treatment and 2. the effect of taper or stop MTX on the effectiveness and the long term TNFi drug survival. Methods: Data was obtained from the DREAM registry. Patients with RA started TNFi treatment in combination with MTX were included in this study. Drug survival of the TNFi was analysed using Cox proportional hazard model with taper or stop MTX as time-dependent covariate. Treatment effectiveness before and after taper or stop MTX was analysed using DAS28. Linear mixed models was used to analyse the difference of DAS28 over time (variable time) between taper and not taper (interaction term = no taper*time) and stop and not stop MTX. Analyses were corrected for possible confounders. Results: Of the 1331 patients starting TNFi with MTX, 487 (36.6%) patients tapered their MTX and 177 of the 1331 (13.3%) stopped their MTX treatment. On average the DAS28 scores decrease after tapering (-0.39, -0.45) and after stopping MTX (-0.26, -0.06) at 6 and 12 month respectively. About 61% of the patients shows an improvement in DAS28 (DAS28<0), 18% shows an increase between 0 and 0.6 DAS28 scores, and 21% shows an increase of >0.6. On average patients that taper or stop have both stable DAS28 scores over time, the same course over time was showed, compared to patients that do not taper or stop MTX (Interaction no taper*time: B=0.00; CI=-0.01:0.00; p=0.339 and interaction no stop*time: B=0.00; CI=-0.01:0.01; p=0.647 respectively). Moreover, the long term drug survival of TNFi is even better in patients tapering MTX and the same in patients stopping MTX, see Table . Conclusions: In daily practice, patients with RA do taper or stop their MTX dose when using TNFi treatment. This does not seem to influence the average DAS28 over time or the long term TNFi drug survival. This indicates that the right/correct patients are chosen to taper or stop MTX treatment in daily practice which could increase the quality of life in these patients. Disclosure of Interest: None declared